Ecological restoration of the Los Angeles River provides natural and human benefits as part of a virtuous socioecological cycle - Katagi, Wendy; Butler, Nate; Keith, Anthony; Backlar, Shelly; Orr, Bruce (Frontiers in Ecology and Evolution, 2022)
Ecological restoration in the Los Angeles (LA) River watershed is proceeding on multiple fronts with the support and engagement of diverse stakeholder groups. Pilot projects to restore habitat, reintroduce native species, and design science-based ecosystem enhancements have produced real benefits to nature and people and demonstrated the potential for additional benefits. The pilot projects, which are in various stages of collaborative planning and implementation, have generated increased interest and financial support to further their implementation and maximize socioecological co-benefits. This self-reinforcing positive feedback is an example of a virtuous cycle established through a combination of long-term environmental planning, community-building, and watershed-scale scientific study to gain the support of stakeholders and align ecological intervention (i.e., restoration) with the plans and policies of governments, resource managers, conservation groups, and grassroots advocacy groups. Conservation and restoration projects targeting iconic and protected focal species can be an effective means of leveraging these interests and building support. For example, the LA River Fish Passage and Habitat Structures project addresses a critical limiting factor for the recovery of endangered steelhead trout (Oncorhynchus mykiss) while also enhancing urban biodiversity and providing recreational opportunities and other beneficial uses (e.g., ecosystem services) for the surrounding communities. Through these efforts, our planners, ecologists, and engineers are using place-based conservation to demonstrate solutions to problems that affect people and nature in other urban landscapes. Here, we show how this work can provide socioecological benefits in disadvantaged communities and also generate public awareness and motivation to perpetuate the cycle of positive feedback.